Ambiguities of a metaphor: the american century - Rodrigues , João Botelho Veloso (2019)
The present work entitled “From the ambiguities of a century of power to the power of a dream” aims to reflect on the hegemonic and global power relations of America throughout the twentieth century, not only reporting on its hegemony, but also on all your ambiguities. In a second moment, it aims to reflect on the challenges and threats that the American power faces when facing the continuation or breaking of the world leadership: The analysis of two proposals that point out the necessary conditions for the operationalization of a new world leadership is made. , led by America.